Individual Public Transportation Accessibility is Positively Associated with Self-Reported Active Commuting - Djurhuus, Sune; Hansen, Henning Sten; Aadahl, Mette; Glümer, Charlotte (Frontiers in Public Health, 2014)
Background: Active commuters have lower risk of chronic disease. Understanding which of the, to some extent, modifiable characteristics of public transportation that facilitate its use is thus important in a public health perspective. The aim of the study was to examine the association between individual public transportation accessibility and self-reported active commuting, and whether the associations varied with commute distance, age and gender. Methods: 28,928 commuters in the Capital Region of Denmark reported self-reported time spent either walking or cycling to work or study each day and the distance to work or study. Data were obtained from the Danish National Health Survey collected in February to April 2010. Individual accessibility by public transportation was calculated using a multimodal network in a GIS. Multilevel logistic regression was used to analyze the association between accessibility, expressed as access area, and being an active commuter. Results: Public transport accessibility area based on all stops within walking and cycling distance was positively associated with being an active commuter. Distance to work, age and gender modified the associations. Residing within 10 km commuting distance and in areas of high accessibility was associated with being an active commuter and meeting the recommendations of physical activity. For the respondents above 29 years, Individual public transportation accessibility was positively associated with being an active commuter. Women having high accessibility had significantly higher odds of being an active commuter compared to having a low accessibility. For men the associations were insignificant.Conclusions: This study extends the knowledge about the driving forces of using public transportation for commuting by examining the individual public transportation accessibility. Findings suggest that transportation accessibility supports active commuting and planning of improved public transit accessibility has